(untitled) (Herald of the National Children’s Medical Center, 2024)
One of the causes of congenital intestinal obstruction is disorders of rotation and fixation of the middle intestine – intestinal malrotation (MC). According to the unanimous opinion of specialists, in case of MC, taking into account life-threatening complications, emergency or planned surgical treatment is indicated to establish a diagnosis. Despite the successes achieved in the surgical treatment of ICD, complications that occur intraoperatively and in the postoperative periods significantly worsen its results.